2020
DOI: 10.1177/1066480720950421
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Self-Compassion on Mindful Parenting: A Mediation Model of Gratitude

Abstract: Mindful parenting, a concept that has been coined and examined recently, refers to a parent’s ability to bring complete attention to their children in the present moment. The aims of this study are to examine the relationship between self-compassion and mindful parenting and the role of gratitude as a mediating variable in a cross-sectional study. Participants include 522 Vietnamese mothers ( M age = 35.17; SD = 5.56) randomly selected through an online investigation. A 26-item Self-Compassion Scale was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 34 publications
(45 reference statements)
1
25
0
Order By: Relevance
“…According to our expectations, mothers’ self‐compassion was shown to be significantly and positively associated with mindful parenting, which is in line with previous research (Nguyen et al., 2020 ). Mothers who are more self‐compassionate tend to hold their painful thoughts and feelings in balanced awareness (Neff, 2003 ), and tend to blame themselves less often for their parenting behaviors because they have a greater sense of common humanity (Moreira et al., 2016 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to our expectations, mothers’ self‐compassion was shown to be significantly and positively associated with mindful parenting, which is in line with previous research (Nguyen et al., 2020 ). Mothers who are more self‐compassionate tend to hold their painful thoughts and feelings in balanced awareness (Neff, 2003 ), and tend to blame themselves less often for their parenting behaviors because they have a greater sense of common humanity (Moreira et al., 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, since the context of the pandemic shares several characteristics with other risk and stressful contexts, that have a potential negative impact on mother–infant relationships and parenting, this knowledge may provide important insights that could be applied outside of the COVID‐19 pandemic. Based on a previously available investigation, we expected higher levels of self‐compassion to be associated with less impaired mother–infant bonding through higher levels of mindful parenting (Nguyen et al., 2020 ) and lower levels of parenting stress (Moreira et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Cronbach’s α was 0.92 for the overall scale. In previous study, the confirmatory factor analysis (CFA) showed that the measurement model yielded an adequate fit at: χ 2 /df = 3.07 ( p < .001), a comparative fit index (CFI) = 0.89, a Tucker-Lewis index (TLI) = 0.87, standardized root-mean-square residual (SRMR) = 0.06, root mean square error of approximation (RMSEA) = 0.06, and 90% confidence interval [CI: 0.06, 0.07], indicating acceptable construct validity for the Vietnamese version (Nguyen et al, 2020). In the present study, the CFA showed that the measurement model yielded an adequate fit at: χ 2 / df = 4.05 ( p < .001), a CFI = 0.89, a TLI = 0.87, SRMR = 0.07, RMSEA = 0.08, and 90% CI [0.07, 0.08], indicating acceptable construct validity.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, researchers found that participants who reported high scores on the Self-Compassion Scale (SCS-26) also scored high on the Gratitude scale (GQ-6). A recent study by Nguyen et al (2020) also shows that self-compassion has helped to improve individuals’ gratitude, and self-compassion interventions increased positive psychological characteristics, including gratitude (Bluth & Eisenlohr-Moul, 2017). From the aforementioned arguments and evidence, we assume that gratitude can play a mediation role in the relationship between self-compassion and psychological well-being during the time of the COVID-19 pandemic.…”
Section: Self-compassion and Psychological Well-beingmentioning
confidence: 99%
“…Additionally, self-compassion is also associated with positive results in parenting, among parents of children and adolescents, such as less parenting stress, improved children’s well-being (Moreira et al, 2015 ), and higher levels of mindful parenting (Nguyen et al, 2020 ). Additionally, parents reporting higher levels of self-compassion were found to be less critical and to use fewer distressed reactions to cope with their children’s emotions (Psychogiou et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%